2010
DOI: 10.1124/dmd.110.035956
|View full text |Cite
|
Sign up to set email alerts
|

The Intestine As an Important Contributor to Prasugrel Active Metabolite Formation In Vivo

Abstract: ABSTRACT:Prasugrel [2-acetoxy-5-(␣-cyclopropylcarbonyl-2-fluorobenzyl)-4,5,6,7-tetrahydrothieno[3,2-c]pyridine], a thienopyridine antiplatelet agent, undergoes rapid hydrolysis in vivo to a thiolactone intermediate, 2-[2-oxo-6,7-dihydrothieno[3,2-c]pyridin-5(4H)-yl]-1-cyclopropyl-2-(2-fluorophenyl)ethanone (R-95913), which is further converted to a pharmacologically active metabolite, 2-[1-2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4-mercapto-3-piperidinylidene acetic acid (R-138727), by oxidation via cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The results suggested that AADAC is involved in prasugrel hydrolysis in human intestine and liver. The high CL int value in HIMs suggests that a large portion of prasugrel was hydrolyzed in the intestine after oral administration, as previously reported (Hagihara et al, 2011). The K m value by recombinant CES1 in this study (16.7 6 1.9 mM) was similar to that reported in a previous study using purified CES1 (9.3 6 0.8 mM) (Williams et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results suggested that AADAC is involved in prasugrel hydrolysis in human intestine and liver. The high CL int value in HIMs suggests that a large portion of prasugrel was hydrolyzed in the intestine after oral administration, as previously reported (Hagihara et al, 2011). The K m value by recombinant CES1 in this study (16.7 6 1.9 mM) was similar to that reported in a previous study using purified CES1 (9.3 6 0.8 mM) (Williams et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…In dogs, both CES1 and CES2 are expressed in the liver but not in the intestine (Taketani et al, 2007). Although substrates of CES enzymes are predicted to be unlikely hydrolyzed in the dog intestine, a previous study reported that the dog intestinal S9 fraction showed prasugrel hydrolase activity comparable to the human intestinal S9 fraction (Hagihara et al, 2011). This result made us hypothesize that enzyme(s) other than CES2 are involved in prasugrel hydrolysis.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…4A). In support of this possibility, hydrolysis of the antiplatelet agent prasugrel was comparable between the small intestine and liver in dogs (Hagihara et al, 2011). …”
Section: Discussionmentioning
confidence: 87%